PENANAMAN KARAKTER RELIGIUS MELALUI PEMBIASAAN SHOLAT DHUHA DI RA HIDAYATUS SHIBYAN BANGSALSARI JEMBER - Diana Ningsih; Irfan Masrur (Jurnal Al-Fatih, 2025)
In addition to being a place to gain knowledge, educational institutions, especially Early Childhood Education institutions, need to be designed as a means for children to learn about character. To achieve maximum character development, it is necessary to make habits that support this. In this case, RA Hidayatus Shibyan Bangsalsari Jember carried out several habituation activities. One of the habituation activities carried out to form the religious character of students is through the habit of praying dhuha every morning before learning begins. This study aims to describe the cultivation of religious character through the habit of dhuha prayer at RA Hidayatus Shibyan Bangsalsari Jember. The research method used by the author is a descriptive qualitative research method, the subjects of this research are teachers, guardians, students and the principal of RA Hidayatus Shibyan. The results of the study show that through the habit of dhuha prayer activities at RA Hidayatus Shibyan, it can instill religious character in early childhood, namely students who are able to appreciate and obey their religious teachings, intended so that children have a basic understanding, beliefs, and love for the Islamic religion they follow which can cause good behaviors from children